1989
DOI: 10.1002/j.1460-2075.1989.tb03477.x
|View full text |Cite
|
Sign up to set email alerts
|

The mammalian G protein rhoC is ADP-ribosylated by Clostridium botulinum exoenzyme C3 and affects actin microfilaments in Vero cells.

Abstract: Clostridium botulinum C3 is a recently discovered exoenzyme that ADP‐ribosylates a eukaryotic GTP‐binding protein of the ras superfamily. We show now that the bacterially‐expressed product of the human rhoC gene is ADP‐ribosylated by C3 and corresponds in size, charge and behavior to the dominant C3 substrate of eukaryotic cells. C3 treatment of Vero cells results in the disappearance of microfilaments and in actinomorphic shape changes without any apparent direct effect upon actin. Thus the ADP‐ribosylation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
288
1
3

Year Published

1990
1990
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 515 publications
(303 citation statements)
references
References 38 publications
(17 reference statements)
10
288
1
3
Order By: Relevance
“…Similar data have been reported for rho C protein expressed in E. coil and was attributed to formation of 1-3) and of small G proteins by C3 (lanes 4-6) was performed as in [14] two conformational isomers of the same protein [4]. When reconstituted with urea-treated ROS membranes, labelling of either band by C3 was decreased by illumination (Fig.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…Similar data have been reported for rho C protein expressed in E. coil and was attributed to formation of 1-3) and of small G proteins by C3 (lanes 4-6) was performed as in [14] two conformational isomers of the same protein [4]. When reconstituted with urea-treated ROS membranes, labelling of either band by C3 was decreased by illumination (Fig.…”
Section: Resultssupporting
confidence: 83%
“…Therefore, we used these membranes to study whether the light regulation of C3 substrates observed in crude ROS membranes is due to a direct interaction of rhodopsin with the small G proteins. Since rho proteins (A, B and C) are substrates of C3 [4,[9][10][11][12][13], we used recombinant human rho A protein expressed in E. coli for the reconstitution with urea-treated ROS membranes. As is shown herein, ADP-ribosylation of rho A protein by C3 is regulated by light when studied in this reconstitution assay in a manner similar to endogenous C3 substrates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The switch regions are structural hallmarks of guanine nucleotide-binding proteins and undergo dramatic conformational changes upon nucleotide exchange, which is required for the downstream signaling (Vetter and Wittinghofer 2001). ADP-ribosylation of this asparagine residue renders Rho biologically inactive and leads to a dramatic and lethal redistribution of actin in the target cell as a consequence (Chardin et al 1989;Paterson et al 1990;Wiegers et al 1991). The mechanism underlying the inactivation of Rho by C3-mediated ADPribosylation was analyzed in great detail.…”
Section: Functional Consequence Of the Adp-ribosylationmentioning
confidence: 99%